Matters of Success: A Deliberative Polling Approach to the Study of Student Retention. (February 2014) - Brown, Tucker; Kenney, Matthew T.
In this article, the authors discuss a recent study they carried out at a mid-sized state university that used a polling method called deliberative polling. This type of polling differs from conventional polling in that respondents are polled before and after a deliberative session in which they discuss issues based on pertinent and empirically-grounded information. This method, it is argued, uncovers observations and insights that could prove valuable to improving university retention and graduation rates.